Proximate Analysis: Content of Red Dragon Fruit Peel - Astuti, Endah Puji; Susanti, Dwi; Suwarno, Suwarno (Disease Prevention and Public Health Journal, 2025)
Background: The dragon fruits have the beneficial, including antioxidants, anti-inflammatory, antimicrobial, properties, blood sugar regulation, and can be used as an ingredient in cosmetics. The purpose of the study was to identify the active compunds contains in Dragon fruits peels using proximate analysis approach. Method: In this study, The proximate analysis was used to measure the contents of water, materials, protein, fat, carbohydrate, crude fiber, energy, Fe, vitamin C and E content, and beta carotene content in the laboratory process. Results: The proximate test results showed that the moisture content of dragon fruit peel flour was 6.3732% - 6.5158%, ash content was 4.8069% - 4.6173%, protein content was 9.2396% - 9.4276%, fat content was 0.4807% - 0.3646%, carbohydrate content was 28.5208% - 28.4530%, crude fiber content was 50, 5788% - 50.6217%, energy content 238.5314 cal/100g - 238.4489 cal/100g, mineral content 2.8993 mg/100g - 2.8747 mg/100g, vitamin C content 16.9835 mg/100g - 25.4752 mg/100g, beta carotene content 5.4672 μg/100g - 4.7922 μg/100g. Conclusion: Research shows that dragon fruit peelc contains various nutrients and bioactive compounds that are beneficial for health Background: The dragon fruits have the beneficial, including antioxidants, anti-inflammatory, antimicrobial, properties, blood sugar regulation, and can be used as an ingredient in cosmetics. The purpose of the study was to identify the active compunds contains in Dragon fruits peels using proximate analysis approach. Method: In this study, The proximate analysis was used to measure the contents of water, materials, protein, fat, carbohydrate, crude fiber, energy, Fe, vitamin C and E content, and beta carotene content in the laboratory process. Results: The proximate test results showed that the moisture content of dragon fruit peel flour was 6.3732% - 6.5158%, ash content was 4.8069% - 4.6173%, protein content was 9.2396% - 9.4276%, fat content was 0.4807% - 0.3646%, carbohydrate content was 28.5208% - 28.4530%, crude fiber content was 50, 5788% - 50.6217%, energy content 238.5314 cal/100g - 238.4489 cal/100g, mineral content 2.8993 mg/100g - 2.8747 mg/100g, vitamin C content 16.9835 mg/100g - 25.4752 mg/100g, beta carotene content 5.4672 μg/100g - 4.7922 μg/100g. Conclusion: Research shows that dragon fruit peelc contains various nutrients and bioactive compounds that are beneficial for health